2017
DOI: 10.1186/s13071-017-2220-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sublethal exposure to metofluthrin on the fitness of Aedes aegypti in a domestic setting in Cairns, Queensland

Abstract: BackgroundMetofluthrin is highly effective at reducing biting activity in Aedes aegypti. Its efficacy lies in the rapid onset of confusion, knockdown, and subsequent kill of a mosquito. In the field, there are a variety of scenarios that might result in sublethal exposure to metofluthrin, including mosquitoes that are active at the margins of the chemical’s lethal range, brief exposure as mosquitoes fly in and out of treated spaces or decreasing efficacy of the emanators with time. Sublethal effects are key el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Additionally, there are other circumstances where mosquitoes may get unintentional sublethal exposures. It has suggested that the time it takes for the vapours to penetrate into surroundings can lead to reduced exposure of target mosquitoes [ 26 , 27 ]. Our findings also support that mosquitoes that may escape spatial repellents can still incur various side-effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there are other circumstances where mosquitoes may get unintentional sublethal exposures. It has suggested that the time it takes for the vapours to penetrate into surroundings can lead to reduced exposure of target mosquitoes [ 26 , 27 ]. Our findings also support that mosquitoes that may escape spatial repellents can still incur various side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although we monitored for mortality and reproductive performance for one week after exposure and blood-feeding, there may be long-term effects of sublethal exposures beyond the first gonotrophic cycle that should be examined. Exposure concentrations also can be controlled by time and have been recognised as a relevant limiter for volatile pyrethroids when the vapours must travel and penetrate into areas of interest [ 26 , 27 ]. To make the findings of our proof of concept study more relevant to field conditions, a valuable next step would be to test short exposure durations.…”
Section: Discussionmentioning
confidence: 99%
“…This leaves movement trajectories in between release and recapture locations unobserved, making it challenging to quantify the relative contributions of multiple competing effects that could account for observed individual-level outcomes under a multitude of equally plausible scenarios. One recent study [ 22 ] showed that even short periods of transient exposure to volatile SRs can have significant, and sometimes delayed, effects on vectors. Such unobserved effects may compromise traditional statistical analyses.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti bloodfed memiliki kebugaran yang tinggi dibandingkan unfed, sehingga mampu bertahan dari tekanan selektif insektisida, serta dapat meningkatkan kelangsungan hidup dan tingkat reproduksi nyamuk. 16,17 Penelitian sebelumnya di laboratorium menyimpulkan bahwa dibutuhkan tingkat konsentrasi insektisida yang tinggi untuk mengubah Ae. aegypti bloodfed dari status rentan menjadi resisten dibandingkan dengan unfed.…”
Section: Pembahasanunclassified